Range matching method based on TCAM:C-TCAM - Guo-sheng ZHU; Shao-hua YU (Tongxin xuebao)
A new TCAM range matching method called C-TCAM(compressed TCAM) was proposed.Firstly C-TCAM could compress two expanded TCAM entries into one and the expansion factor of w-1 and w-2 respectively in the worst case.Secondly,a new TCAM matching algorithm to lower down the power dissipation was designed by avoiding matching of unnessary TCAM entries.Analysis and simul ion showed that C-TCAM gets advantages over other schemes in TCAM space efficiency and power dissipation.